2006
DOI: 10.1007/s10658-006-9072-x
|View full text |Cite
|
Sign up to set email alerts
|

Host range expansion in a powdery mildew fungus (Golovinomyces sp.) infecting Arabidopsis thaliana: Torenia fournieri as a new host

Abstract: Since 2003, Torenia fournieri plants grown for experimental purposes were repeatedly infected by powdery mildew in a laboratory in Hungary. Based on morphological characteristics, the pathogen belonged to the mitosporic genus Oidium subgen. Reticuloidium, the anamorph stage of Golovinomyces. The rDNA ITS sequence was identical to that of two other powdery mildew fungi, infecting Arabidopsis and Veronica, respectively, in different parts of the world. According to a previous phylogenetic analysis of ITS and 28S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
(22 reference statements)
0
26
0
Order By: Relevance
“…Some authors have argued that high host specificity does not exclude possibilities for host shifts/host jumps, i.e., evolutionary lability (Parker and Gilbert 2004). Indeed, host jumps and host shifts are thought to be major driving forces in powdery mildew evolution (Vági et al 2007;Hirose et al 2005) and have also been recognized in the evolution of rust fungi, another group of highly specialized biotrophic pathogens (Roy 2001). It seems that at least some powdery mildew fungi possess pathogenicity factors that allow them to establish a compatible parasitic relationship with allopatric plant species, e.g., upon introduction of the fungi in a new region (Vági et al 2007); this might be one of the reasons why Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have argued that high host specificity does not exclude possibilities for host shifts/host jumps, i.e., evolutionary lability (Parker and Gilbert 2004). Indeed, host jumps and host shifts are thought to be major driving forces in powdery mildew evolution (Vági et al 2007;Hirose et al 2005) and have also been recognized in the evolution of rust fungi, another group of highly specialized biotrophic pathogens (Roy 2001). It seems that at least some powdery mildew fungi possess pathogenicity factors that allow them to establish a compatible parasitic relationship with allopatric plant species, e.g., upon introduction of the fungi in a new region (Vági et al 2007); this might be one of the reasons why Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, host jumps and host shifts are thought to be major driving forces in powdery mildew evolution (Vági et al 2007;Hirose et al 2005) and have also been recognized in the evolution of rust fungi, another group of highly specialized biotrophic pathogens (Roy 2001). It seems that at least some powdery mildew fungi possess pathogenicity factors that allow them to establish a compatible parasitic relationship with allopatric plant species, e.g., upon introduction of the fungi in a new region (Vági et al 2007); this might be one of the reasons why Fig. 2 Relative performance benefit of local versus distant interactions in cross-inoculations between strains of oak powdery mildew (Erysiphe alphitoides sensu lato) and Quercus robur progenies (asterisk, significant difference between local and distant interactions) powdery mildews have been reported as one of the most successful group of invasive species among fungi (Kreisel and Scholler 1994;Jones and Baker 2007;Desprez-Loustau et al 2010b).…”
Section: Resultsmentioning
confidence: 99%
“…This latter situation has arisen quite frequently during the past years because some powdery mildew fungi have recently become invasive in certain areas (Cook et al 2006;Seko et al 2008;Heluta et al 2009), and/or have shown up on plant species which have not been previously reported to host them (e.g., Vági et al 2007;Jankovics et al 2008). In such cases, a portion of the species do not produce the teleomorph stage regularly, or do not produce them at all, and this makes their identification difficult (Cunnington et al 2003;Takamatsu et al 2007;Vági et al 2007;Jankovics et al 2008;Kiss et al 2008;Seko et al 2008). In all the above mentioned studies, the ITS sequences were determined using direct sequencing of the PCR products.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that germination tests done for species identification purposes have often been set up on artificial surfaces. These included glass slides (Zaracovitis 1965;Fletcher et al 1988), water agar (Vági et al 2007), lid of a plastic Petri dish (Cook and Braun 2009) and non-host plant materials such as epidermis of onion scale (To-anun et al 2005). In some cases, however, germinated conidia were collected directly from host plant surfaces and investigated to support the identification of the powdery mildews infecting the source plant species (e.g., Kiss et al 2001;Liberato 2006) or for other purposes (Oichi et al 2006;Nonomura et al 2009b).…”
mentioning
confidence: 99%